1998
DOI: 10.1017/s0950268898008899
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of campylobacter infections in broiler flocks by application of hygiene measures

Abstract: Transmission routes of Campylobacter spp. in broilers and possibilities for prevention of infections were studied on two Dutch broiler farms. The occurrence of Campylobacter spp. was studied in successive broiler flocks, in the environment of the farms and in some of the parent flocks involved. Isolates of Campylobacter spp. were typed by using randomly amplified polymorphic DNA (RAPD) analysis. The results indicate that broiler flocks become infected from environmental sources. The typing results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 28 publications
6
95
1
5
Order By: Relevance
“…Certainly, water cups become campylobacter positive at about the same time that flocks become positive (6). Detection of C. jejuni in broiler house water sources prior to stocking and flock positivity has proved difficult (106). However, in natural water supplies, shearing forces, high oxygen concentration, UV, nutrient deprivation, and antimicrobials all cause the bacteria to become environmentally stressed.…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
“…Certainly, water cups become campylobacter positive at about the same time that flocks become positive (6). Detection of C. jejuni in broiler house water sources prior to stocking and flock positivity has proved difficult (106). However, in natural water supplies, shearing forces, high oxygen concentration, UV, nutrient deprivation, and antimicrobials all cause the bacteria to become environmentally stressed.…”
Section: Sources Of Poultry Colonizationmentioning
confidence: 99%
“…According to different studies, infection on chicken farms could enter the flock by vertical transmission from parent flocks , or by horizontal transmission via different sources (Pearson et al, 1993;van de Giessen et al, 1998;Petersen & Wedderkopp, 2001;Hiett et al, 2002;Hansson et al, 2007). Groundwater is frequently used as drinking water in poultry farms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have indicated that applied hygienic practices and barriers as well as the type of the ventilation system can be associated with the risk of Campylobacter infection of broiler flocks (Van de Giessen et al, 1998;Evans and Sayers, 2000;Barrios et al, 2006;Hald et al, 2007;McDowell et al, 2008;Hansson et al, 2010). The analyses of the EU-wide baseline survey on Campylobacter in broiler batches and carcases indicated that the previous thinning of the flock, the age of the broilers and the quarter of sampling (3-month period) were associated with Campylobacter-colonised broiler batches (EFSA, 2011c).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%